Yield of robusta coffee in different spatial arrangements - Espindula, Marcelo Curitiba; Rocha, Leonardo Barreto; Schmidt, Raquel; Rocha, Rodrigo Barros; Dias, Jairo Rafael Machado; Bravin, Maísa Pinto; Partelli, Fábio Luiz (Pesquisa Agropecuaria Brasileira, 2022)
The objective of this work was to determine the contribution of the number of stems to the composition of individual plant yield, and to individual and overall robusta coffee (Coffea canephora) yield at different planting densities, using a fixed number of stems per plant. The experiment was carried out in two phases. The first phase was performed from 2011 to 2015, in the municipality of Ouro Preto do Oeste, in the state of Rondônia (RO), Brazil, to evaluate different numbers of stems per plant (1, 2, 3, 4, 5, and 6). The second phase was conducted from 2013 to 2018, in the municipality of Alta Floresta D’Oeste, RO, to evaluate plant densities (at 1,666, 1,904, 2,222, 2,666, and 3,333 plants ha-1), with an initial density of four stems per plant in all treatments. The increase of number of stems per plant promotes a quadratic response to the average and cumulated yield of coffee plants, and the maximum yield is attained with four stems per plant. The number of stems should not exceed four, to avoid their tipping during years of high production. Plant density of 3,333 plants per hectare, with 4 stems per plant and 1 m spacing, promotes the reduction of individual plant yield; however, it results in higher overall crop yield.